Do sovereign bond spreads in inflation targeting economies reflect creditworthiness and anticipate stress scenarios? - Hatcherian, Georges (2012)
Fil: Hatcherian, Georges. Universidad de San Andrés. Escuela de Administración y Negocios; Argentina.